The Influence of Performance, Information and Communication on Community Satisfaction at the East Simeulu District Office - Ilhamuddin, Dody; Hasyim, Hasyim; Fatimah, Fatia (Institute of Computer Science (IOCS), 2024)
This study uses quantitative research methods to establish correlations between multiple variables to examine the impact of performance, information, and communication on community satisfaction. The findings indicate that performance partially influences community satisfaction, with a t-value of 5.791, which exceeds the critical t-table value of 1.985, and a significance level below 0.05 (p = 0.000). However, the information variable shows no significant influence on community satisfaction, as the t-value of 1.575 is below the critical t-table value of 1.985 at a significance level of 0.119 > 0.05. Similarly, the communication variable also fails to impact community satisfaction significantly, with a t-value of 1.118, below the critical t-table value, and a significance level of 0.266 > 0.05. Conversely, when considering the simultaneous influence of performance, information, and communication on community satisfaction, the results reveal a significant effect, with an F-value of 50.727 > the critical F-table value of 2.70 at a significance level of 0.000 < 0.05. Performance and communication are influential factors in satisfaction, while the information variable does not demonstrate a significant influence. This research concludes that while performance and communication positively affect satisfaction, information does not significantly influence satisfaction levels among East Simeulue and Simeulue Aceh Regency residents.